Analisis Rencana Tata Ruang dan Wilayah (RTRW) dalam Pemenuhan Kebutuhan Ruang Terbuka Hijau (RTH) Kota Tegal - Dwian Hartomi Akta Padma Eldo; Arief Zulfyka Maulana (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2020)
Development in urban areas increased with the advent of the and increase the number of, so needs for city infrastructures have also been developed. So is required Planning and The Analysis Spatial (RTRW) In meeting the needs of green space (RTH). Will discuss research based on it on efforts to city government tegal in planning RTRW, RTF as restrictions on in fulfilling this study. Motode used in this study is by using the method descriptive qualitative by granting a factual. happening on the ground The research results show that the seriousness of the government as a form of City Tegal in doing, Planning had spent legislation no. 4 years 2012 City Tegal about spatial plans and regions of the need green space .But until the moment only 15 new % RTH have been fulfilled of 30 % the space in the city tegal based on the no. 4 years 2012.